Establishment of an Agrobacterium‐mediated genetic transformation and CRISPR/Cas9‐mediated targeted mutagenesis in Hemp (Cannabis Sativa L.). Issue 10 (23rd June 2021) - Zhang, Xiaoyu; Xu, Gencheng; Cheng, Chaohua; Lei, Lei; Sun, Jian; Xu, Ying; Deng, Canhui; Dai, Zhigang; Yang, Zemao; Chen, Xiaojun; Liu, Chan; Tang, Qing; et al.
Summary: Hemp ( Cannabis sativa L.) is an annual and typically dioecious crop. Due to the therapeutic potential for human diseases, phytocannabinoids as a medical therapy is getting more attention recently. Several candidate genes involved in cannabinoid biosynthesis have been elucidated using omics analysis. However, the gene function was not fully validated due to few reports of stable transformation for Cannabis tissues. In this study, we firstly report the successful generation of gene‐edited plants using an Agrobacterium ‐mediated transformation method in C . sativa . DMG278 achieved the highest shoot induction rate, which was selected as the model strain for transformation. By overexpressing the cannabis developmental regulator chimera in the embryo hypocotyls of immature grains, the shoot regeneration efficiency was substantially increased. We used CRISPR/Cas9 technology to edit the phytoene desaturase gene and finally generated four edited cannabis seedlings with albino phenotype. Moreover, we propagated the transgenic plants and validated the stable integration of T‐DNA in cannabis genome.